Development of a high-efficient transformation system of Bacillus pumilus strain DX01 to facilitate gene isolation via gfp-tagged insertional mutagenesis and visualize bacterial colonization of rice roots - Shen, Xinqian; Chen, Yunpeng; Liu, Tong; Hu, Xiaolu; Gu, Zhenfang (Folia microbiologica, 2013)
A Tn5 transposition vector, pMOD-tet-egfp, was constructed and used for the random insertional mutagenesis of Bacillus pumilus. Various parameters were investigated to increase the transformation efficiency B. pumilus DX01 via Tn5 transposition complexes (transposome): bacterial growth phase, type of electroporation buffer, electric field strength, and recovery medium. Transformation efficiency was up to 3 × 10(4) transformants/μg of DNA under the optimized electroporation conditions, and a total of 1,467 gfp-tagged transformants were obtained. Fluorescence-activated cell sorting analysis showed that all gfp-tagged bacterial cells expressed GFP, indicating that foreign DNA has been successfully integrated into the genome of B. pumilus and expressed. Finally, flanking DNA sequences were isolated from several transformants and colonization of rice roots by B. pumilus DX01 was also studied. The method developed here will be useful for creating an insertion mutant library of gram-positive bacteria, thus facilitating their molecular genetic and cytological studies.
Keywords: elektroporace; bakteriální transformace; genetické vektory; zelené fluorescenční proteiny; rýže (rod); Green Fluorescent Proteins; inzerční mutageneze; Transformation, Bacterial; Culture Media; barvení a značení; kultivační média; Oryza; Flow Cytometry; DNA Transposable Elements; Electroporation; Bacillus; Mutagenesis, Insertional; Genetic Vectors; průtoková cytometrie; Staining and Labeling; transpozibilní elementy DNA